Synthesis of 4-tert-Butyltoluene by Vapor Phase tert-Butylation of Toluene with tert-Butylalcohol over USY Zeolite - Yanming Shen; Shan Yuan; Lihui Fan; Dongbin Liu; Shifeng Li (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
Vapour phase tert-butylation of toluene with tert-butylalcohol was studied over ultra-stable Y zeolite (USY) catalyst. The effects of reaction temperature, toluene/TBA molar ratio and liquid space velocity on conversion of toluene and selectivity for 4-tert-butyltoluene were studied. The deactivation and regeneration of the catalyst was also investigated. The results showed that the USY zeolite catalyst offered better toluene conversion of about 30 % and 4-tert-butyltoluene selectivity of about 89 % at the suitable reaction condition as follows: reaction temperature of 120 oC, toluene/TBA ratio of 2:1 and liquid space velocity of 2 ml/g·h. The clogging of mocropores by the formed carbon or oligomers was the main reason for the deactivation of the catalyst. By combustion at 550 oC, the catalyst just lost about 5 % in toluene conversion and about 2 % in PTBT selectivity. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)